1987
DOI: 10.1007/bf00594200
|View full text |Cite
|
Sign up to set email alerts
|

Fluid trapping of erythrocytes under hypoosmolar conditions

Abstract: 125I albumin was used to assess the amount of trapped fluid after microhematocrit centrifugation of erythrocytes suspended in buffers of different osmolality. Surprisingly the total amount of trapped fluid per volume unit of packed erythrocytes decreased with decreasing osmolality of the suspending buffer despite erythrocyte swelling. However, if the contribution of the individual erythrocyte to the trapped fluid was calculated, the trapped fluid per erythrocyte did not change between 311 mosm/kg and 256 mosm/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We emphasize that lowered plasma osmolarity is found in several clinical syndromes including inappropriate antidiuretic hormone secretion and diuretic therapy [10]. As reported in the earlier study [10], the swollen erythrocytes may, in general, produce some difficulties in the blood capillary or splenic passage but the aforementioned conditions are not associated with impairment of oxygen transport or hemolysis of clinical significance.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…We emphasize that lowered plasma osmolarity is found in several clinical syndromes including inappropriate antidiuretic hormone secretion and diuretic therapy [10]. As reported in the earlier study [10], the swollen erythrocytes may, in general, produce some difficulties in the blood capillary or splenic passage but the aforementioned conditions are not associated with impairment of oxygen transport or hemolysis of clinical significance.…”
Section: Introductionmentioning
confidence: 60%
“…As reported in the earlier study [10], the swollen erythrocytes may, in general, produce some difficulties in the blood capillary or splenic passage but the aforementioned conditions are not associated with impairment of oxygen transport or hemolysis of clinical significance. It is of interest to note that swollen erythrocytes have been employed during the encapsulation of non-diffusible drugs into human erythrocytes (used for drug delivery and targeting) [11].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been shown that osmolalities below 250 mOsm/kg increase the sphericity of RBCs to a point, where the trapping of suspending medium between RBCs during centrifugation gradually increases, which leads to an overestimation of MCV. 26 This may explain the non-linear increase of MCV and decrease of MCHC at very low osmolalities shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 95%
“…This volume is registered by the microhematocrit as intracellular volume, but not in the NMR hematocrit. Trapped extracellular fluid has been experimentally demonstrated to compose 1.6-2% of the total cell volume at approximately 30% hematocrit using identical microhematocrit tubes, spinning times, and range of osmolalities as in this investigation (26). The corresponding values for this investigation are probably 1-2% higher at the range of hematocrits used here (27).…”
Section: Resultsmentioning
confidence: 80%